Evaluation of ROS-TAC Score and DNA Damage in Fertile Normozoospermic and Infertile Asthenozoospermic Males - Vatannejad, Akram; Tavilani, Heidar; Sadeghi, Mohammad Reza; Amanpour, Saeid; Shapourizadeh, Somyeh; Doosti, Mahmood (Urology Journal, 2017)
Purpose: The aim of study was to evaluate reactive oxygen species (ROS), total antioxidant capacity (TAC) andROS-TAC score as indicator for oxidative stress status as well as 8-hydrodeoxyguanosine (8-OHdG) levels as amarker for DNA damage in the seminal plasma of asthenozoospermia patients compared to normozoospermiasamples. Materials and Methods: The semen samples of 28 fertile normozoospermic donors and 25 infertile men withasthenozoospermia were analyzed according to World Health Organization (WHO) criteria. ROS production wasmeasured in neat semen samples by the chemiluminescent assay. Plasma levels of TAC was measured by commercially available colorimetric assays. The levels of DNA oxidative damage were measured by seminal plasma levelsof 8-OHdG using ELISA method. ROS-TAC score was measured using principal component analysis. Results: Asthenozoospermic men had a higher ROS levels compared to the normozoospermic men (P = .01).However, no significant difference was observed in TAC levels between the groups. ROS-TAC score in asthenozoospermicmen was lower than normozoospermic men (P = .02). The levels of 8-OHdG in the asthenozoospermicmen were higher than normozoospermic men (P = .01). Conclusion: The present study demonstrated a decrease in ROS-TAC score and, a high DNA damage in asthenozoospermiacompared to normozoospermia. ROS-TAC score can predict the oxidative damage of semen samplesof astenozoospermic infertile males.